Cue Utilization Predicts Resource Allocation during Rail Control Simulations: A NIRS Study. (September 2018) - Sturman, Daniel; Wiggins, Mark W.; Auton, Jaime C.; Loft, Shayne
This study was designed to examine whether cue utilization differentiates performance and resource allocation during simulated monitoring and process control tasks. The experiment involved the completion of a 45-minute rail control simulation that required participants to re-route trains either infrequently (monitoring task) or periodically (process control task). Implicit patterns of train movement were incorporated into the rail control task. Measures of participants' response latency, fixation rates and cerebral blood flow were taken. Participants with higher cue utilization demonstrated greater decreases in fixation rates, smaller changes in cerebral oxygenation in the prefrontal cortex, and smaller increases in response latencies. The results provide support for the assertion that a relatively greater capacity for cue utilization is associated with the allocation of fewer cognitive resources during sustained attention tasks.